Who cares about sanctions? Observations from annual reports of European firms - Davydov, Denis; Sihvonen, Jukka; Solanko, Laura (Taylor & Francis, 2022)
This paper uses textual analysis to examine how European corporations assess sanctions in their annual reports. Using observations from a panel of almost 11,500 corporate annual reports from 2014 to 2017, we document significant cross-country variation in how firms perceive Russia-related sanctions, even after controlling for many firm-level characteristics, sectoral differences, and time trends. The cross-country differences also remain for sentiments about sanctions and contexts in which sanctions are mentioned. We also examine the role of macroeconomic linkages in explaining these differences. We show that Russia’s inward and outward FDI stocks and high levels of imports and exports with Russia explain about half of the cross-country variation, leaving a nontrivial share of variation unexplained.
Keywords: textual analysis; european firms; annual reports; sanctions; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|